Analisis Peran Account Officer dalam Meminimalisir Pembiayaan Bermasalah di PT. BPRS Gajahtongga Kotopiliang - Shela Kurnia Putri; Sandra Dewi (Universitas 45 Surabaya, 2024)
The research was motivated was by the unsatisfactory work system carried out by account officers for customers and the lack of self-awareness of customers regarding the financing carried out so that financing problems often occur every year PT. BPRS Gajahtongga Kotopiliang. This type of research is descriptive qualitative field research, namely research that tries to describe, explain and interpret a phenomenon regarding the role of account officers in minimizing financing problems at PT. BPRS Gajahtongga Kotopiliang. The data collection technique in this research was interviews by visiting the PT office directely BPRS Gajahtongga Kotopiliang as well as documntation to obtait written data related to this thesis. Based on the results of the research conducted, it can be concluded that the analysis of the role of account officers in minimizing problematic financing at PT. BPRS Gajahtongga Kotopiliang is analyzing financing applications that refer to the 5C principles, namely, character, capacity, capital, condition of economy, and collateral. Factors causing financing problems at PT. BPRS Gajahtongga Kotopiliang is caused by the bank (internal) and the customer (external). Techniques for resolving problematic financing at PT. BPRS Gajahtongga Kotopiliang is to reschedule (reconditioning) and restructuring.